Effect of plantation age on plant and soil C:N:P stoichiometry in Kentucky bluegrass pastures - Wei, Xiaoxing; He, Keyan; Wang, Qian; Liu, Wenhui; Pang, Xiaopan; Guo, Zhenggang (Frontiers in Sustainable Food Systems, 2024)
Plant and soil C:N:P stoichiometry reflects the element content and energy flow, which are important for biogeochemical cycling in ecosystems. Although plantation age has been verified to affect leaf C:N:P stoichiometry in alfalfa plants, its effect on plant and soil C:N:P stoichiometry in grass remains poorly documented. A 10-year field experiment of Kentucky bluegrass (Poa pratensis) was used to test how plantation age affect plant and soil C:N:P stoichiometry in a perennial rhizomatous grass pasture. This study demonstrated that leaf C:N, C:P, and N:P ratios exhibited a rapid increasing trend from 2 to 6 years of age, whereas leaf C:N showed a slight decreasing trend, and leaf C:P and N:P maintained stability from 6 to 9 years of age. Stem C:N and N:P were not different among plantation ages, while stem C:P increased from 2 to 4 years of plantation age and then maintained stability from 4 to 9 years of plantation age. Root N:P showed an increasing trend from 2 to 6 years of plantation age and relative stability from 6 to 9 years of plantation age, whereas root C:N and C:P showed decreasing trends from 2 to 9 years of plantation age. Although soil C:P did not differ among nine plantation ages, soil C:N and N:P remained relatively stable from 2 to 6 years of plantation age. However, soil C:N showed a decreasing trend, while soil N:P showed an increasing trend after 6 years of plantation age. The results from an ecological stoichiometric homeostasis analysis further showed that N in the leaf, stem, and root and P in the stem had strict homeostasis, whereas P in the leaf and root showed plastic and weakly homeostatic status, respectively. These results present a pattern concerning the plantation age in relation to plant and soil C:N:P stoichiometry in a perennial grass and provide useful information for N and P management in Kentucky bluegrass pastures.